Modeling the modulation of beta oscillations in the basal ganglia by dual-target optogenetic stimulation - Xiaomin Wang; Ying Yu; Qingyun Wang (Fundamental Research)
Optogenetic techniques provide precise control over the activity of specific neurons within the nucleus, offering more accurate regulatory effects compared to deep brain stimulation. The heterogeneity of the globus pallidus externa (GPe) has garnered wide attention, wherein significant differences in pathological changes emphasize its potential as a stimulation target with distinct mechanisms. A basal ganglia-thalamus (BG-Th) network model incorporating heterogeneous GPe is developed to explore potential optogenetic stimulation targets for treating Parkinson's disease (PD). Initially, the modulation mechanisms of single-target optogenetic stimulation on the abnormal rhythmic oscillations of BG nuclei are examined. Excitation of D1 medium spine neuron (MSN), calcium-binding protein parvalbumin (PV) GPe, and inhibition of globus pallidus interna (GPi) can effectively suppress synchronous bursting activity in GPi, while excitation of GPi promotes high-frequency discharge to disrupt beta oscillations. Furthermore, dual-target optogenetic stimulation strategies are devised to reduce energy consumption. Results show that targets with similar mechanisms exhibit additive effects, whereas targets with opposing mechanisms lead to cancellation. The underlying effective mechanisms of dual-target strategies are: enhancing the inhibitory input to GPi thus inhibiting the activity of GPi, or disrupting beta oscillations by restoring high-frequency discharges in GPi. The strategy composed of exciting D1 MSN and inhibiting GPi requires the minimum total light intensity among single-target and dual-target strategies in our simulation. Furthermore, simultaneously enhancing PV GPe and inhibiting D2 MSN achieves the greatest reduction in total energy consumption (40.8% reduction), compared to only enhancing PV GPe. The findings unveil effective circuit mechanisms of optogenetic stimulation and provide novel insights for designing precise regulatory strategies for PD.